Organization of club sports and improving and sports work on the place of study, residence - Oleg V. Shinkarenko; Dmitry V. Logunov (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article specifies the students’ skills of having a healthy and sport way of life, the ability of this activity organization that will provide them with the conditions for keeping fit. That is important for conducting their educational activity that meets the requirements of federal state educational standards for students. The formation of the bases of the health improving methods has become actual. The following problems are revealed in the article: an insufficient quantity of sports facilities, the poor organization of work on a place of study, the lack of the coordinated work of turning the youth to the physical culture and sport. There is a problem of preparation for standards of the GTO complex. The system of measures for the solution of these problems is suggested: to increase the quantity of youth going in for mass physical culture and sport; to carry out preparation of youth for standards of the GTO complex at a higher and qualitative level.